Workplace Bullying and Turnover Intention: Moderating Role of Abusive Supervision among Employees of Nepali Commercial Banks (Quest Journal of Management and Social Sciences, 2022)
Background: Organizations are facing many explicit and implicit costs associated with the voluntary turnover of high-performing employees. Voluntary turnover is detrimental to organizational growth and success. Therefore, employers and practitioners try to understand what motivates people to leave. Negative employee behaviors such as workplace bullying and abusive supervision have been identified as critical variables for employee motivation to leave.Purpose: The purpose of the paper was to investigate the moderating role of Abusive Supervision in relation to Workplace Bullying and Turnover Intention among employees in Nepali Commercial Banks.Research Methodology: This paper applied a quantitative approach and cross-sectional survey research design to investigate the research objective. The convenience sampling method was employed to research employees of different commercial banks. Data were collected from 202 employees via self-administered questionnaires. Covariance-Based Structure Equation Modeling (CB-SEM) was applied to examine research hypotheses.Results: The result showed that Workplace Bullying positively influences Turnover Intention among employees of Nepali commercial banks. Also, the result showed that Abusive Supervision moderates the relationship between Workplace Bullying and Turnover Intention.Conclusion: According to the paper, employees of Nepali commercial banks intend to leave their respective banks if they experience Workplace Bullying at a different level of Abusive Supervision. Increasing Abusive Supervision in the presence of Workplace Bullying increases the intention of leaving commercial banks.Implications: This paper has two implications. Theoretically, this paper provides a critical juncture for Nepali researchers by investing in moderating the role of Abusive Supervision on turnover intention. Managerially, it is imperative for organizations to invest in enriching their employees by creating a work environment free of bullying and abusive supervision.Originality: This paper stands at a critical juncture in Nepali research because it is among the fewest studies investigating the moderating role of abusive supervision on workplace bullying and turnover intention.